2012
DOI: 10.3139/120.110380
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Deep Cryogenic Treatment on Mechanical and Tribological Properties of PM S390 MC High-Speed Steel

Abstract: Application of deep cryogenic treatment instead of conventional heat treatment showed an increase in wear resistance of tools made of high speed steel which are exposed to very complex and demanding conditions in exploitation. The purpose of this study was to investigate the effect of deep cryogenic treatment in combination with plasma nitriding on the tribological properties of powder metallurgy high speed steel, grade PM S390 MC. On treated specimens hardness and fracture toughness was determined, the resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…One can note a difference in the height and width of the maximum, which indicated that the microstructure of martensite is small-grained, i. e. needles in martensite are finer in the deep cryogenic treated specimens, which is in agreement with the effects of deep cryogenic treatment [5,9,10,13].…”
Section: Chemical Analysis and Structural Propertiessupporting
confidence: 65%
See 1 more Smart Citation
“…One can note a difference in the height and width of the maximum, which indicated that the microstructure of martensite is small-grained, i. e. needles in martensite are finer in the deep cryogenic treated specimens, which is in agreement with the effects of deep cryogenic treatment [5,9,10,13].…”
Section: Chemical Analysis and Structural Propertiessupporting
confidence: 65%
“…The results showed that deep cryogenic treatment followed by plasma nitriding contributed to the increase in the adhesive and abrasive wear resistance of the PM S390 MC high speed steel [13].…”
Section: Resultsmentioning
confidence: 90%
“…Nitriding in the duration of 2.5 hours was carried out at a temperature of 490 °C in a Metalplas Ionon BDAG GRUPPE BALCKE-DÜRR AG apparatus. After heat treatment, thorough analysis of the microstructure and mechanical properties was performed on samples and the results were published in [19].…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the coefficient of friction, DCT samples had a bit higher coefficient of friction, approximately 4 % higher than classically heat-treated samples. Through nitrogen diffusion layer formation [19,20], plasma nitriding reduced friction coefficient of the analysed steel in classic heat-treated samples (HTN) and DCTN samples for 8 % and 11 %, respectively. Fig.…”
Section: Figure 3 Flank Wear Of the Tool Vbmentioning
confidence: 99%
“…Solid shot as microcutting teeth scrape tool surface. Material particles, ejection chips or particles periodically collapsing outgrowth, having hardness close to the material hardness, drag on contact surfaces, carry a certain amount of material and leave traces in the form of scratches [5][6][7].…”
Section: Introductionmentioning
confidence: 99%